Strategic communication for organizations - LaBelle, Sara, 1988-; Waldeck, Jennifer H. (University of California Press, 2020)
"This book is divided into two main sections. The first section, Foundations of Strategic Communication (Chapters One-Four), provides an understanding of the myriad organizational types and structures that engage in strategic communication, as well as how organizations define and brand themselves to create a cohesive identity. Ethical communication is spotlighted in the first section as a key to maintaining organizational value and creating effective campaigns. The second section, Creating, Implementing, and Evaluating Strategic Messages (Chapters Five-Eleven), lays out a step-by-step plan for creating strategic communication campaigns that align with the organization's identity and mission as well as for aligning campaigns with the needs of stakeholders and communication partners. In these chapters we discuss how organizations can organize and prepare for effective campaigns by having clear objectives, a thorough understanding of their target audience, an evidence-based approach to messaging, and in carefully selecting both traditional and new media platforms. Throughout this section, we attend to the cultural diversity that exists across campaign stakeholder groups and how that diversity should inform communication strategy. Finally, we address the importance of implementing and evaluating communication campaigns. You will learn a variety of strategies for assessing campaigns to identify successes, and make adjustments to your strategic communication plan moving forward"--Provided by publisher